NCCBM, a Nomogram Prognostic Model in Breast Cancer Patients With Brain Metastasis - Liu, Qiang; Kong, Xiangyi; Wang, Zhongzhao; Wang, Xiangyu; Zhang, Wenxiang; Ai, Bolun; Gao, Ran; Fang, Yi; Wang, Jing (Frontiers in Oncology, 2021)
Nomogram prognostic model could greatly facilitate risk stratification and treatment strategies for cancer patients. We developed and validated a new nomogram prognostic model, named NCCBM, for breast cancer patients with brain metastasis (BCBM) using a large BCBM cohort from the SEER (Surveillance Epidemiology and End Results) database. Clinical data for 975 patients diagnosed from 2011 to 2014 were used to develop the nomogram prognostic model. The predictive accuracy and discriminative ability of the nomogram were determined by concordance index (C-index) and calibration curve. The results were validated using an independent cohort of 542 BCBM patients diagnosed from 2014 to 2015. The following variables were selected in the final prognostic model: age, race, surgery, radiation therapy, chemotherapy, laterality, grade, molecular subtype and extracranial metastatic sites. The C-index for the model described here was 0.69 (95% CI, 0.67 to 0.71). The calibration curve for probability of survival showed good agreement between prediction by nomogram and actual observation. The model was validated in an independent validation cohort with a concordance index of 0.70 (95% CI, 0.68 to 0.73). We developed and validated a nomogram prognostic model for BCBM patients and the proposed nomogram resulted in good performance.